Assessment of urbanization growth using GIS and remote sensing in Gumel Town Jigawa State of Nigeria - Gumel Muhammad Lawan, Ali; Mohd Khairul Amri, Kamarudin (2020)
Urbanization extensions at the expense of the surrounding land corresponding generally to land use land cover. Therefore, this study tried to come up with the urbanization growth based on land use land cover change from 1998 to 2018 using GIS and remote sensing in Gumel town Nigeria. Remotely sensed imagery combined with GIS served to evaluate the typical land use land cover dynamics. The supervised classification was used to generate land use land cover classes for the study area. The result shows that settlements and bare land classes arc increased about 0.99% in 1998 to 1.77% in 2018 and 48.94% in 1998 to 72.89% in 2018 respectively, while vegetation and shrub land for land use land cover classes are decreased by 9.41% to 5.26% and 40.66% to 20.08% in 2018. The factors responsible for this change are natural and artificial, which include population growth, deforestation and desert encroachment. The study further suggests to reduces overgrazing and cutting down of trees for fuel as the shrub land helps to fight wind erosion which is responsible for bare land in the area. As highlighted by this study, combining remote sensing and GIS could be an effective approach to land use land cover planning and improving the environment.